Diverse Microbial Composition of Sourdoughs From Different Origins - Comasio, Andrea; Verce, Marko; Van Kerrebroeck, Simon; De Vuyst, Luc (Frontiers in Microbiology, 2020)
Hundreds of sourdoughs have been investigated in the last decades. However, many studies used a culture-dependent and/or culture-independent microbiological approach [mainly based on denaturing gradient gel electrophoresis (DGGE) of PCR amplicons], seldomly combined with a metabolite target analysis, to characterize the microbial species communities of the sourdoughs examined. Moreover, attention was mainly paid on lactic acid bacteria (LAB) and yeast species. In the present study, distinct household- (including an artisan lambic brewery) and artisan bakery-scale backslopped sourdoughs (17 in total), obtained from different regions (Belgium, France, United Kingdom, and USA), were examined through a multiphasic approach, encompassing a culture-dependent analysis [targeting LAB, acetic acid bacteria (AAB), and yeasts], different culture-independent techniques [rRNA-PCR-DGGE, metagenetics, and metagenomics (four bakery sourdoughs)], and metabolite target analysis. It turned out that the microbial species diversity of the sourdoughs was influenced by the house microbiota of the producer. Further, when the producer made use of different flours, the sourdoughs harbored similar microbial communities, independent of the flour used. AAB were only present in the Belgian sourdoughs, which might again be related to the processing environment. Fructilactobacillus sanfranciscensis (formerly known as Lactobacillus sanfranciscensis) was the prevalent LAB species of the eight sourdoughs produced by two of the three bakeries analyzed. These sourdoughs were characterized by the presence of either Saccharomyces cerevisiae or Kazachstania humilis. Moreover, the presence of Fl. sanfranciscensis was positively correlated with the production of mannitol and negatively correlated with the presence of other LAB or AAB species. Sourdoughs produced in an artisan lambic brewery were characterized by the presence of the yeast species Dekkera anomala and Pichia membranifaciens. One household sourdough was characterized by the presence of uncommon species, such as Pediococcus parvulus and Pichia fermentans. Metagenomic sequencing allowed the detection of many more LAB and AAB species than the other methods applied, which opened new frontiers for the understanding of the microbial communities involved during sourdough production processes.